Comparison of Symptom Control in Pediatric Gastroparesis Using Endoscopic Pyloric Botulinum Toxin Injection and Dilatation. Issue 3 (2nd September 2021) - Mercier, Clémence; Ley, Delphine; Aumar, Madeleine; Lemale, Julie; Fabre, Alexandre; Colinet, Stéphanie; Duhamel, Alain; Gottrand, Frédéric
ABSTRACT: Objectives: The objective of this study was to assess the tolerance and efficacy of endoscopic intrapyloric botulinum toxin injection compared with pyloric dilatation in children with gastroparesis. Methods: This was a retrospective descriptive multicentre study that included pediatric patients treated between 2010 and 2018 at 4 tertiary hospitals. Results: Data were collected for 24 patients. The median age at diagnosis was 2.5 years (range 0.5–4.7). A total of 46 endoscopic procedures were performed. The endoscopic procedure was multiple in 63% of patients. Among the interventions, 76% were successful and 15% were unsuccessful. The recurrence rate was 57% and the median time to recurrence was 3.7 months (0.1–73). The efficacy did not differ significantly between the 2 methods at the first intervention and as a second-line treatment. The recurrence rate also did not differ significantly between the 2 methods. No complications were reported. The median follow-up was 19.8 months (1.7–61.7). Conclusions: In this retrospective multicentre study, endoscopic management of gastroparesis by balloon dilatation or botulinum toxin was safe in children and seemed to be partially efficient within the first months. Symptoms recurred frequently and required repetition of the interventions.